2017
DOI: 10.4238/gmr16019315
|View full text |Cite
|
Sign up to set email alerts
|

Association between the interleukin-1β C-511T polymorphism and periodontitis: a meta-analysis in the Chinese population

Abstract: ABSTRACT. The association between the interleukin-1 beta (IL-1β) C-511T (or rs16944) polymorphism and periodontitis remains inconclusive, even though there have been previous studies on this association. To assess the effects of IL-1β C-511T variants on the risk of development of periodontitis, a meta-analysis was performed in a single ethnic population. Studies, published up to December 2015, were selected for the meta-analysis from PubMed and Chinese databases. The associations were assessed with pooled OR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The IL-1β rs16944 polymorphism is associated with susceptibility to periodontitis in the European 20 and the Chinese population. 26 However, another report showed no significant association between the IL-1β rs16944 polymorphism and CP susceptibility. 27 The link between the IL-1β rs1143627 polymorphism and susceptibility to periodontitis is even weaker.…”
Section: Clinical Evidence Regarding Interleukin(il)-1βmentioning
confidence: 99%
“…The IL-1β rs16944 polymorphism is associated with susceptibility to periodontitis in the European 20 and the Chinese population. 26 However, another report showed no significant association between the IL-1β rs16944 polymorphism and CP susceptibility. 27 The link between the IL-1β rs1143627 polymorphism and susceptibility to periodontitis is even weaker.…”
Section: Clinical Evidence Regarding Interleukin(il)-1βmentioning
confidence: 99%
“…We found that the IL1B -511 T/T genotype was associated to the risk of periodontitis in nonsmokers and in all subjects in this Southern Brazilian population. Previous findings had showed that the T allele was associated to periodontitis in Afro-Americans and Mulattos from the southeastern region of Brazil [68] and also in the Chinese population as shown in two meta-analysis studies [8,9]. The T/T genotype in codominant (T/T vs. C/C) and dominant (C/T + T/T vs. C/C) inheritance models were also associated to PD in Chinese [8].…”
Section: Discussionmentioning
confidence: 86%
“…Previous findings had showed that the T allele was associated to periodontitis in Afro-Americans and Mulattos from the southeastern region of Brazil [68] and also in the Chinese population as shown in two meta-analysis studies [8,9]. The T/T genotype in codominant (T/T vs. C/C) and dominant (C/T + T/T vs. C/C) inheritance models were also associated to PD in Chinese [8]. Otherwise, in a cohort study conducted in Japanese pregnant women, the -511 C/T genotype showed a protective association to periodontitis after the adjustment of the odds ratio [69].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This phenomenon has been linked to a wide range of disorders, in which there is an altered inflammatory response, such as rheumatoid arthritis, psoriasis or inflammatory bowel disease as well as other pathologies (e.g., cancer) ( 11 , 12 ). At the oral level, polymorphisms of IL-1 have been widely studied in relation to periodontal disease ( 19 ). More recently, an attempt has been made to identify whether these polymorphisms are related to an augmented risk for early dental implant failure or peri-implantitis ( 16 - 18 ).…”
Section: Resultsmentioning
confidence: 99%